Creative Destruction and Regional Productivity: Evidence from the Polish Regions in 2004–2015 - Kuźmar, Sławomir (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
A considerable and persisting diversity of the development levels of Polish regions makes it necessary to seek potential causes of this phenomenon. It can be presumed that some of the diversity is caused by institutional qualities, characteristic for each individual region, including the dynamics of the reallocation of resources available in a particular region, which can be identified with the creative destruction processes, indicated by J. A. Schumpeter. In the view of these facts, this study aims at identifying the mechanisms of creative destruction processes and assessing their influence on the levels of regional productivity of labour in Poland, in the 2004–2015 time period. The conducted analyses showed that the correlation between the measures of creative destruction and the labour productivity is ambiguous and limited, as it was confirmed for only a part of Polish regions. For the remaining part, contrary to the theoretical assumptions, a reverse relationship was observed, i.e. it is the dynamics of productivity that affects the level of reallocation of resources, identified with the processes of creative destruction.